The Regional security problem and course of Egypt (1980-2000) - Жaнaтaевa, К. Б. (Journal of Oriental Studies, 2018)
The growing religious extremism in the last quarter of the 20th century influenced the political situation of the Arab countries, including Egypt. The issue of religious extremism and terrorism has become one of the most pressing problems in the Arab region. Now in 70 countries there are thousands of groups and organizations that combine their activities with terrorist attacks. According to observers, about 200 of them use Islam as their ideology. The development of terrorism in Egypt is undoubtedly due to political instability and economic difficulties. To stabilize the internal situation in the country, the country’s leadership is conducting a “gradual democratization” of the society. This course provides for signs of liberalization.